A HYBRID FRAMEWORK FOR SECURE DEVICE-TO-DEVICE COMMUNICATION IN WIRELESS SYSTEMS USING BLOCKCHAIN AND ONION ROUTING - Jadhav, Kiran Bhavlal; Nigam, Manoj Kumar; Shinde, Sagar Bhilaji (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This study introduces a hybrid architecture that uses Blockchain and onion routing to solve important privacy and security issues with Device-to-Device (D2D) communication in wireless networks. The need for secure communication is growing in tandem with the number of Internet of Things (IoT) devices, leaving traditional D2D systems open to typical dangers like eavesdropping and man-in-the-middle (MITM) attacks. To improve user privacy and data security, the suggested system combines onion routing's multilayer encryption with Blockchain's decentralised authentication. The performance, security resilience, and resource utilisation of the framework were evaluated thoroughly. The results showed that the attack success rates were significantly lower than those of previous models. With its benefits in protecting sensitive communications, the hybrid framework is especially well-suited for applications in smart cities, healthcare, and finance, despite the fact that it does incur greater latency and resource demands. The research results support the use of hybrid security solutions in D2D communication, which strike a balance between security and performance. In the future, we will optimise this framework to operate better in contexts with limited resources and look into other ways to make it even better at securing user data in our linked world.